2007
DOI: 10.1021/jf0627120
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Oat-Based Biorefinery for the Production of l(+)-Lactic Acid by Rhizopus oryzae and Various Value-Added Coproducts

Abstract: A novel oat-based biorefinery producing L(+)-lactic acid and various value-added coproducts (e.g., beta-glucan, anti-irritant solution) is proposed. Pearling is employed for sequential separation of bran-rich fractions for the extraction of value-added coproducts. Lactic acid production is achieved via fungal fermentation of Rhizopus oryzae on pearled oat flour. Maximum lactic acid concentration (51.7 g/L) and starch conversion yield (0.68 g/g) were achieved when an oat flour concentration of 116.5 g/L was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This suggests that this fermented beverage could embrace greater flavour attributes as it has been reported that acetaldehyde is a major flavour component in yoghurt and other yoghurtrelated milks imparting a unique 'yoghurt' aroma (Coda et al, 2011;Ott, Fay, & Chaintreau, 1997;Ott, Germond, Baumgartner, & Chaintreau, 1999). The aroma of acetaldehyde has been described as 'green','ethereal' and 'pungent' (Koutinas, Malbranque, Wang, Campbell, & Webb, 2007). It has been observed that, during the fermentation of water-based cereal puddings inoculated with lactic acid bacteria the values of acetaldehyde were less than 1.0 mg/kg, and in milk-based cereal puddings the same strains produced acetaldehyde in concentrations that varied from 1.0 to 4.5 mg/kg (Helland et al, 2004).The rest of the cereal beverages had values of acetaldehyde from 0.13 to 0.24 mg/L.…”
Section: Acetaldehyde Ethanol and Acetonementioning
confidence: 82%
“…This suggests that this fermented beverage could embrace greater flavour attributes as it has been reported that acetaldehyde is a major flavour component in yoghurt and other yoghurtrelated milks imparting a unique 'yoghurt' aroma (Coda et al, 2011;Ott, Fay, & Chaintreau, 1997;Ott, Germond, Baumgartner, & Chaintreau, 1999). The aroma of acetaldehyde has been described as 'green','ethereal' and 'pungent' (Koutinas, Malbranque, Wang, Campbell, & Webb, 2007). It has been observed that, during the fermentation of water-based cereal puddings inoculated with lactic acid bacteria the values of acetaldehyde were less than 1.0 mg/kg, and in milk-based cereal puddings the same strains produced acetaldehyde in concentrations that varied from 1.0 to 4.5 mg/kg (Helland et al, 2004).The rest of the cereal beverages had values of acetaldehyde from 0.13 to 0.24 mg/L.…”
Section: Acetaldehyde Ethanol and Acetonementioning
confidence: 82%
“…11,23 An oat starch conversion yield of 68 g LA/100 g starch was achieved in 10 L airlift bioreactors when spores were used as inoculum. 24 Sweet potato starch produced 72 g LA from 100…”
Section: Discussionmentioning
confidence: 99%
“…oryzae spores were inoculated into 100 mL of Vogel medium containing 3% (w/v) triticale starch at a final spore concentration at PEER REVIEW 1×10 4 per mL. One gram of sterile calcium carbonate powder was added to the culture medium at 0, 16,20,24, and 40 h during the fermentation at 28°C. To determine the effect of CaCO 3 dosage on LA production, different amounts of CaCO 3 were added to the medium 24 h after start of the fermentation.…”
Section: Effect Of Calcium Carbonate On the Kinetics Of La Fermentationmentioning
confidence: 99%
“…Fermentative conversion of saccharides into platform chemicals would be dependent on the development of viable biorefineries (Koutinas et al, 2004a;Koutinas et al, 2004b;Webb et al, 2004;Koutinas et al, 2006;Koutinas et al, 2007a;Koutinas et al, 2007b;Koutinas et al, 2007c;Koutinas et al, 2007d). A generic strategy leading to fermentative conversion of various biomass resources into platform chemicals is shown in Figure 4.2.…”
Section: Chemical Production From Saccharidesmentioning
confidence: 99%